Representation of mental illness in Christian self-help bestsellers - Webb, Marcia (Mental health, religion & culture, 2008)
The present study examined messages about mental illness in 14 contemporary Christian self-help bestsellers. Content analysis revealed that most texts focused upon depression. Categories of textual units included Underlying Assumptions Regarding Depression, Representations of Depression, Roots/Causes/Reasons for Depression, and Christian Responses to Depression. Demonic influence was the most frequently cited reason for depression. Other reasons included negative cognitions, failure as a Christian, and negative emotions. Christian responses to depression included trusting God, religious activity, and individual willpower. Discussion of these results focused upon the problematic impact of these messages upon individuals with depression, and upon suggestions for reducing mental illness stigma in religious communities.